Partisipasi Masyarakat dalam Pelestarian Lingkungan di kawasan Pantai Padang - Bleszeinsky, Gabby (JESS (Journal of Education on Social Science); Vol 3 No 1 (2019): Relationship between Government and Community, 2019)
This study aims to determine the Community Participation in Environmental Conservation in the Padang Coast area, to find out the supporting and inhibiting factors in Community Participation in Environmental Conservation in the Padang Beach area, to find out the efforts of the Padang City Culture and Tourism Office in increasing community participation in environmental conservation. This research is a qualitative research with descriptive method. This research was conducted in the Padang Beach Area, Cimpago Beach and Muaro Lasak. Research informants were determined by purposive sampling. Data collected is in the form of secondary data and primary data through interviews, observation and documentation studies. The validity test of the data is done by triangulation and then the data is analyzed by reducing data, displaying data and drawing conclusions during the study. The results of this study indicate that there is still a lack of community participation in the coastal Padang area. Supporting factors found were environmental preservation programs from the Padang city cultural and tourism services and support from the leadership. The inhibiting factors are lack of public awareness, inadequate facilities and infrastructure, lack of awareness from tourists. Keywords: Community Participation, Environmental Conservation